Uncovering Negotiation Through Translating Cultural Identity in Formal Documents: A Case Study of UNESCO Agreements - Syafran, Ahmad; Roselani, Ni Gusti Ayu (Journal of English Language Teaching, Linguistics, and Literature Studies, 2025)
This study investigates how Indonesian cultural identity has been constructed and negotiated through agreements with UNESCO and examines its influence on global awareness, cooperation, and collaboration. A descriptive-qualitative analysis was conducted on 414 pages of Indonesian–English contract texts available in UNESCO’s online repository, focusing on cultural-specific words and items classified according to Ahimsa-Putra and Rachman’s (2021) taxonomy and coded as either resistance or negotiation following Venuti and Eco. The analysis involved descriptive coding using definitions from the Kamus Besar Bahasa Indonesia and the Oxford English Dictionary, Source–Target Relations (STR) analysis to identify shifts, thematic categorization of translation strategies, and interpretive analysis based on Derrida’s concepts of meaning shifts and différance. A conceptual framework was developed to ensure semantic alignment and control for potential confounders during validation of meaning connotation, with authoritative dictionaries used to validate the lexicon and cross-literature checks conducted to compare our dataset with established literature anchors. The findings indicate that direct equivalence translation is infrequent, with contrastive searches for equivalents often resulting in faithful representation in terms of meaning, identity, and culture, and that generative description reveals nuanced relationships between translation choices and the representation of cultural identity.Keywords: Cultural identity, Cultural references, Negotiation, Translation, UNESCO Agreements